The Magic Screen A History of Regent Street Cinema - Hunningher, Joost (University of Westminster Press, 2015)
"The story of the (now restored) Regent Street Cinema is the fourth volume exploring the University of Westminster's long and diverse history. This multi-authored volume tells its history from architectural, educational, legal and cinematic perspectives and is richly illustrated throughout with images from the University of Westminster archive. A print paperback can be purchased direct from the University of Westminster for £20 following this link: www.westminster.ac.uk/historybooks Staff, students and alumni can claim a 20% discount on this price."